Entre casos comoventes e noticiário cotidiano: (in)visibilidades engendradas pela cobertura da violência contra crianças e adolescentes em três jornais mineiros - Eliziane Consolação Lara (2013)
In this paper we investigate the coverage of violence against children and adolescents conducted by three newspapers of the Brazilian state of Minas Gerais: Estado de Minas, O Tempo and Super Notícia. Specifically, we tried to understand how texts published in those journals articulate meanings from a set of presences and absences when reporting cases of violence against children in their homegroup. To develop this analysis, we started with two points for observation: the social representations driven by journalistic discourse and the subjects constructed by news reporting. The selection of texts adopted as temporal reference the death of the five-year-old girl Isabella Nardoni, which occurred in March 2008 and was 8 widely reported by the Brazilian press. Adopting this framework implies that this research includes texts published in the same period of that occurrence and reports taken from the same newspapers one year later. Based on those strategies, we come to a set of texts that allowed us to move from cases that are especially commotional to those type of cases which are daily published in the newspapers without achieving great media repercussion. In general, this work aims to discuss modes of visibility built by newspaper when reporting violent occurrences.